The Importance of Housing Policy in Uzbekistan in Connection with Innovative Economy - Yuldosheva Shakhribonu Anvarqizi (Research Parks Publishers, 2022)
In this article, we have described the housing policy, housing and communal services activities, types of services, ongoing reforms to improve the efficiency of housing and communal services and their main directions.